Highly pathogenic avian influenza H5N1 – a global animal health crisis: Profound challenges to science and society - Joseph, D; Samuel, J.C. (2006)
The H5N1 highly pathogenic avian influenza epizootic is a serious multidimensional challenge to agriculture, rural development and public health and requires high multi sectoral attention for its solution...